Philosophy In-sistencial at present: the in-sistencial communitarian personalism of Ismael Quiles SJ - Sebastián Solanes, Raúl Francisco (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
This text presents the proposal of In-sistencial philosophy developed by Ismael Quiles, analyzing various aspects. The first is to place Quiles in the philosophical and historical context, analyzing his intellectual formation in Spain and in his exile in Argentina, seeing the stages of his thought. Secondly, I see Quiles relations with existentialism of Heidegger, Sartre and Gabriel Marcel. Third, I try to justify that his thinking belongs to the current communitarian personalism, but not shed Buber’s Jewish orientation, but Christian. Lastly argue that despite his adherence to Christianity, we can not consider him just as a Christian philosopher, but as a philosopher who, influenced by Eastern thought, who opens in-sistencial philosophy to mysticism.